2022
DOI: 10.1097/ccm.0000000000005622
|View full text |Cite
|
Sign up to set email alerts
|

Using Qualitative Synthesis to Explore Heterogeneity of Randomized Trials on ICU Diaries*

Abstract: Objective: We aimed to identify which set of components differentiates the ICU diaries that were effective in reducing psychologic symptoms after critical illness. Data Sources: We searched the online databases MEDLINE, OVID, Embase, and EBSCOhost from inception to December 2021. Study Selection: Randomized controlled trials (RCTs) of the ICU diary were included, irrespective of the language, with samples of adult patients (≥ 18 yr old) and/or their relatives hospitalized in an ICU for more than 24 hours. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…A follow-up study by the same authors in 2021 not only concluded positive impressions by patients, family, and staff members related to the use of ICU diaries but also noted that time pressure of ICU staff members writing in diaries may be an overall obstacle for staff diary entries (Barreto et al [11]). Both articles cited above as well as that of Brandao Barreto et al (9) show positive patient and family outcomes with the use of ICU diaries for patients on ventilators. All three studies used existing data from online databases such as PubMed, MEDLINE, OVID, Embase, and EBSCOhost.…”
mentioning
confidence: 85%
See 4 more Smart Citations
“…A follow-up study by the same authors in 2021 not only concluded positive impressions by patients, family, and staff members related to the use of ICU diaries but also noted that time pressure of ICU staff members writing in diaries may be an overall obstacle for staff diary entries (Barreto et al [11]). Both articles cited above as well as that of Brandao Barreto et al (9) show positive patient and family outcomes with the use of ICU diaries for patients on ventilators. All three studies used existing data from online databases such as PubMed, MEDLINE, OVID, Embase, and EBSCOhost.…”
mentioning
confidence: 85%
“…What is most useful from the study by Brandao Barreto et al (9) is the critique the authors give for ongoing use and evaluation of ICU diaries in general and suggestions on how to improve the data from the diary information. Quality improvement suggestions include the need for standardizing the ICU diary process, which would allow for comparison studies on this topic for generalizability as well as for variant differences.…”
mentioning
confidence: 99%
See 3 more Smart Citations